Extracorporeal carbon dioxide removal with the Advanced Organ Support system in critically ill COVID‐19 patients. Issue 12 (21st September 2021) - Allescher, Julia; Rasch, Sebastian; Wiessner, Johannes R.; Perez Ruiz de Garibay, Aritz; Huberle, Christina; Hesse, Felix; Schulz, Dominik; Schmid, Roland M.; Huber, Wolfgang; Lahmer, Tobias
Abstract: Disturbed oxygenation is foremost the leading clinical presentation in COVID‐19 patients. However, a small proportion also develop carbon dioxide removal problems. The Advanced Organ Support (ADVOS) therapy (ADVITOS GmbH, Munich, Germany) uses a less invasive approach by combining extracorporeal CO2 ‐removal and multiple organ support for the liver and the kidneys in a single hemodialysis device. The aim of our study is to evaluate the ADVOS system as treatment option in‐COVID‐19 patients with multi‐organ failure and carbon dioxide removal problems. COVID‐19 patients suffering from severe respiratory insufficiency, receiving at least two treatments with the ADVOS multi system (ADVITOS GmbH, Munich, Germany), were eligible for study inclusion. Briefly, these included patients with acute kidney injury (AKI) according to KDIGO guidelines, and moderate or severe ARDS according to the Berlin definition, who were on invasive mechanical ventilation for more than 72 hours. In total, nine COVID‐19 patients (137 ADVOS treatment sessions with a median of 10 treatments per patient) with moderate to severe ARDS and carbon dioxide removal problems were analyzed. During the ADVOS treatments, a rapid correction of acid‐base balance and a continuous CO2 removal could be observed. We observed a median continuous CO2 removal of 49.2 mL/min (IQR: 26.9‐72.3 mL/min) with some treatments achieving up to 160 mL/min. The CO2 removal significantly correlated with blood flow (Pearson 0.421; P < .001), PaCO2 (0.341, P < .001) and HCO 3 ‐ levels (0.568, P < .001) at the start of the treatment. The continuous treatment led to a significant reduction in PaCO2 from baseline to the last ADVOS treatment. In conclusion, it was feasible to remove CO2 using the ADVOS system in our cohort of COVID‐19 patients with acute respiratory distress syndrome and multiorgan failure. This efficient removal of CO2 was achieved at blood flows up to 300 mL/min using a conventional hemodialysis catheter and without a membrane lung or a gas phase. Abstract : Nine COVID‐19 patients with multiorgan failure (ARDS, AKI, Mechanical Ventilation) and carbon dioxide removal problems received 137 ADVOS treatment sessions (ADVITOS, Munich, Germany). Using a conventional hemodialysis catheter at up to 300 mL/min blood flow and 9.5 dialysate pH, a rapid correction of acid‐base balance and a median continuous CO2 removal of 49.2 mL/min was observed, without a membrane lung or a gas phase. The continuous treatment significantly reduced PaCO2 and was feasible in this cohort of critically ill patients.